Predicted cellular interactors of the endogenous retrovirus-K protease enzyme - Narvey, Samuel; Vandenakker, Alex; Rempel, Megan; Douville, Renée N. (Frontiers in Virology, 2022)
Retroviral proteases are essential enzymes for viral replication and drive changes within the cellular proteome. While several studies have demonstrated that protease (PR) enzymes from exogenous retroviruses cleave cellular proteins and modulate cellular signaling, the impact of PRs encoded by endogenous retroviruses within the human genome has been largely overlooked. One human symbiont called Endogenous retrovirus-K (ERVK) is pathologically associated with both neurological disease and cancers. Using a computational biology approach, we sought to characterize the ERVK PR interactome. The ERVK PR protein sequence was analyzed using the Eukaryotic Linear Motif (ELM) database and results compared to ELMs of other betaretroviral PRs and similar endogenated viral PRs. A list of putative ERVK PR cellular protein interactors was curated from the ELM list and submitted for STRING analysis to generate an ERVK PR interactome. Reactome analysis was used to identify key pathways potentially influenced by ERVK PR. Network analysis postulated that ERVK PR interacts at the apex of several ubiquitination pathways, as well as has a role in the DNA damage response, gene regulation, and intracellular trafficking. Among retroviral PRs, a predicted interaction with proliferating cell nuclear antigen (PCNA) was unique to ERVK PR. The most prominent disease-associated pathways identified were viral carcinogenesis and neurodegeneration. This strengthens the role of ERVK PR in these pathologies by putatively driving alterations in cellular signaling cascades via select protein-protein interactions.